Correlation of Prostate Volume and Intravesical Prostatic Protrusion with Detrusor Wall Thickness using Transabdominal Ultrasonography in Benign Prostate Enlargement: A Preliminary Study - Wijaya, Andre Tjie; Laksminingsih, Nyoman Srie; Dwijaputra, I Made; Raka Widiana, I Gde; Duarsa, Gede Wirya Kusuma; Asih, Made Widhi; Sitanggang, Firman Parulian (JBN (Jurnal Bedah Nasional); Vol 6 No 2 (2022): JBN (Jurnal Bedah Nasional), 2022)
Aim: Assessed the correlation between prostate volume and intravesical prostatic protrusion with detrusor wall thickness through transabdominal sonographic examination of benign prostate enlargement (BPE). Methods: The study is a paired-group analytical observational cross-sectional study during April – July 2020. Measurements were made of prostate volume, intravesical prostatic protrusion, and detrusor wall thickness using transabdominal sonography. An analysis was carried out to determine the correlation with bivariate analysis and the calculation of the research power. Results: Thirty-four BPE patients with a mean age of 62.41 years were included in the study. The mean value of prostate volume obtained was 44.24 cc; 8.66 mm for intravesical prostatic protrusion; and detrusor wall thickness is 1.49 mm. The correlation value between prostate volume and detrusor wall thickness was 0.12 (p=0.46), while the intravesical prostatic protrusion and detrusor wall thickness were 0.37 (p=0.03). The research power for correlating prostate volume with detrusor wall thickness and intravesical prostatic protrusion with detrusor wall thickness was 10-20% and 50-60%, respectively. Conclusion: There is a very weak correlation between prostate volume and detrusor wall thickness and a weak correlation between the intravesical prostatic protrusion and detrusor wall thickness. Other variables may influence the thickness of the detrusor wall.